2021
DOI: 10.1007/s11356-021-13202-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun nanofibers of polyvinylidene fluoride incorporated with titanium nanotubes for purifying air with bacterial contamination

Abstract: Polyvinylidene fluoride (PVDF) blended with varying concentrations of titanium nanotubes (TNT) was electrospun to result in a nanocomposite filter media. Sandwich structures were obtained by depositing the electrospun fibers between polypropylene (PP) nonwoven sheets. The synthesized tubular TNT was confirmed for its morphology through a transmission electron microscope (TEM). The prepared filter media was analyzed through a scanning electron microscope (SEM), X-ray diffraction (XRD), Fourier infrared spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 66 publications
2
15
0
Order By: Relevance
“…As can be seen from Table 2 , the estimated pore size of r-PET and SF mats was larger than that of fibrous composites (except r-PSF7) and showed a decreasing trend with the decrease of fiber diameter. This trend is consistent with other electrospun nanofiber membrane investigations, where the larger pore size is obtained when fiber diameter increased [ 43 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As can be seen from Table 2 , the estimated pore size of r-PET and SF mats was larger than that of fibrous composites (except r-PSF7) and showed a decreasing trend with the decrease of fiber diameter. This trend is consistent with other electrospun nanofiber membrane investigations, where the larger pore size is obtained when fiber diameter increased [ 43 ].…”
Section: Resultssupporting
confidence: 92%
“…Different polymeric materials have been used for producing electrospun membrane for filtration including cellulose acetate (CA) [ 37 ], silk fibroin (SF) [ 38 ], poly(lactic acid) (PLA) [ 39 ], polyamide-6 (PA6), poly(vinyl alcohol) (PVA) [ 40 ], polyvinylacetate (PVAc) [ 37 ], polyacrylonitrile (PAN) [ 41 , 42 ], polyvinylidene fluoride (PVDF) [ 43 ], or poly(ethylene terephthalate) (PET) [ 33 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Air, widespread with bioaerosols ranging from airborne viruses, bacteria, fungi, to pollens, is associated with a variety of adverse health effects, such as allergies, infectious diseases, respiratory illnesses and cancer. Low settling velocity and minute size of the particles are the major reason for these particles to remain in the atmosphere for a longer duration than other aerosols [ 116 , 117 ]. Currently, membrane filtration is thought to be the most effective physical approach against air pollutants.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…Antibacterial and zone of inhibition studies revealed that the prepared filter media was highly efficient against both Escherichia coli and Staphylococcus aureus . In this study, it was found that 15 wt % of the filler proved for the highest bacterial filter efficiency of 99.88% [ 116 ]. PAN/CuO nanofibers were successfully electrospun with varying concentrations of CuO in PAN nanofibers by Hashmi et al From their results, it can be concluded that tensile strength has direct and linear relationship with copper oxide concentration in PAN nanofibers.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…Air, widespread with bioaerosols ranging from airborne viruses, bacteria, fungi, to pollens, is associated with a variety of adverse health eff ects, such as allergies, infectious diseases, respiratory illnesses and cancer. Low settling velocity and minute size of the particles are the major reason for these particles to remain in the atmosphere for a longer duration than other aerosols [116,117]. Currently, membrane fi ltration is thought to be the most eff ective physical approach against air pollutants.…”
Section: Facemaskmentioning
confidence: 99%